Evaluation and Characterization of Cellulose Nanofibers from Flaxseed Fiber Bundles. Issue 4 (July 2021) - Azhar, Sayed Waqar; Xu, Fujun; Qiu, Yiping
In recent decades, rational management of agricultural residues presented a new approach for extraction, characterization, and utilization of cellulose nanofibers (CNF). In this context, the valorization of flaxseed fibers, providing an annual yield of millions of metric tons, as an abundant sustainable fiber source, was carried out. The cleaned and ground raw material was delignified and bleached, followed by 2, 2, 6, 6-tetramethylpiperidine-1-oxyl radical (TEMPO)/NaBr/NaClO oxidization along with mechanical homogenization. The resulting extracted cellulose and cellulose nanofibers were characterized by various analytical methods. The overall yield of CNF based on the raw material was 31.2% ± 1.5%. This study explored a simple method for converting flaxseed fibers to fluorescent, high quality, nano-sized cellulosic precursors for novel applications in pharmaceutical and bio-composite applications.